The legal insignificance of the financial coverage at the bill of exchange and the cheque - Janković Svetislav (Anali Pravnog Fakulteta u Beogradu)
Due to the identical personal structure, the bill of exchange and the cheque have a common feature regarding the drawer's cover on a banking account which is administrated by the drawee. It seems that sufficiency of adequate funds, which should cover the drawer's order from these instruments, doesn't have any legal significance for the drawee and the acceptor. At first glance the position of drawee and acceptor is different because the drawee's obligation is also not derived from the bill of exchange; however, the acceptor has an obligation due to his acceptance of the drawer's order. However, at the stage of collection, drawee and acceptor have a similar position regarding financial cover by drawer's account. Regardless of whether there is financial coverage, the legal position of the drawee and acceptor remains unchanged, because their position could be changed only through their legally relevant will, manifested in the instrument as such.